Fatores associados à deficiência de vitamina a em crianças menores de cinco anos da região semiárida de Alagoas - Moura, Renata Maria de Magalhães (2011)
Vitamin A deficiency is a nutritional deficiency of high magnitude, which may be caused insufficient intake of food sources of vitamin A or problems in their absorption, transport or use. It is an aggravation of great importance due to the negative health effects caused mainly by compromising the immune system, increasing susceptibility to infections and, in severe forms, for damage to vision. Children under five years of a biologicalgroups are most vulnerable to vitamin A deficiency, is of fundamental importance to recognize the risk factors associated with its occurrence and thereby establish better prevention and control. This dissertation is composed of a chapter review of the literature on vitamin A deficiency and developed an original article in order to investigate the factors associated with this disorder in children aged 0 to 59 months of the semiarid region of Alagoas. Through high-resolution liquid chromatography, calculated from this retinol serum of 551 children (probability sample) residing in that region. The prevalence of vitamin A deficiency (serum retinol <20μg/dL) was 45.4%. The factors independently associated (logistic regression) were low birth weight (p = 0.01), lower maternal age (p = 0.012), the lowest duration of breastfeeding (p = 0.041), carrying vaccination card out of date (p = 0.069), low maternal education (p = 0.059) and lack of sanitation in the home (p = 0.056). Therefore, vitamin A is in a serious public health problem in the semiarid region of Alagoas. The factors involved should be considered when planning and implementing prevention and control.